1999
DOI: 10.1021/jp991449l
|View full text |Cite
|
Sign up to set email alerts
|

Recombination Reactions and Diffusive Properties of Diatomic Molecules in Two Different Microporous Structures:  Silicalite and ZK4

Abstract: Computer simulations of the dissociation-recombination reaction of diatomic molecules have been carried out in the pore networks of the zeolites silicalite and ZK4. This kind of processes can provide interesting insights into the effect of the confinement on the reaction dynamics. The diffusion of the species involved in the recombination processes has been separately investigated through equilibrium simulations. Considerable differences between silicalite and ZK4, both in the recombination probability and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…We then proceeded with the study of a dissociation-recombination reaction in silicalite. [4][5][6] Such kind of processes, exploiting many of the specific properties of zeolites, result particularly suitable as a starting point to obtain comparative information on the catalytic activity of different zeolitic hosts. Radical processes are usually not activated, thus a statistically meaningful number of reactive trajectories may be easily generated and examined by dissociating a stable molecule in different initial conditions and following its subsequent dynamics.…”
Section: Computer Simulationsmentioning
confidence: 99%
“…We then proceeded with the study of a dissociation-recombination reaction in silicalite. [4][5][6] Such kind of processes, exploiting many of the specific properties of zeolites, result particularly suitable as a starting point to obtain comparative information on the catalytic activity of different zeolitic hosts. Radical processes are usually not activated, thus a statistically meaningful number of reactive trajectories may be easily generated and examined by dissociating a stable molecule in different initial conditions and following its subsequent dynamics.…”
Section: Computer Simulationsmentioning
confidence: 99%
“…The size of the micropore or cavity plays an important role in the selectivity process. The widespread and diverse uses of zeolites are as catalysts and molecular sieves in the chemical industry and as ion exchangers, in particular as absorbents in detergents. Diffusion phenomena, which are the basis of those applications, lie in the adsorption and the transportation processes. , Interest in the water−zeolite interaction arises from the fact that water plays strong and essential roles for both absorption and catalytic properties of zeolite, , as it is known that all natural zeolites are hydrated. In addition, water molecules facilitate the exchange of the charge-compensating cations, which are essential for the industrial catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Compelling evidence exists that zeolite pore walls act as an efficient third body for halide radicals produced by photodissociation of I 2 , Cl 2 , and Br 2 in the zeolite pores. 22,23,52,53 However, Xu et al found no evidence for zeolites acting as a third body in the coupling of methyl radicals. 54 If collisions with the walls of the zeolite pores can push the rate of the H + OH + M reaction into the high pressure limit (as justified in the ESIw), then in the 200-400 1C temperature range, the pseudo-second-order rate constant for H + OH + M is larger than the rate constant for H + NO 2 by a factor of B1.7.…”
Section: [Nomentioning
confidence: 99%
“…The zeolite walls could potentially act as a third body/collision partner in association reactions and unimolecular decomposition reactions. For example, it has been shown that zeolite pore walls can act as a third body in radical recombination reactions, 22,23 and it has also been speculated that aerosols may act as a third body in the atmosphere. 24 Such effects could alter reaction mechanisms in the zeolite relative to the gas phase at low total pressures.…”
Section: Introductionmentioning
confidence: 99%